Quality of native goat's milk from a multivariate perspective - RIBEIRO, Neila Lidiany; FURTADO, Dermeval Araújo; CHIODI, John Edson; MASCARENHAS, Nágela Maria Henrique; SILVA, Ricardo de Sousa; RODRIGUES , Raimundo Calixto Martins; FARIAS, Brendo Júnior Pereira; NOBRE, Rafaela de Sousa; ARRUDA, Tacila Rodrigues; FIGUEIREDO, Caio Franklin Vieira de; PORTO FILHO, José Mathias; FURTADO, Felipe (Food Science and Technology, 2024)
The aim of this study was to assess the relationship between physical components and the fatty acid (FA) profile of goat's milk, compare the physical and chemical variables of the milk using canonical correlation, and verify the contribution of the physical variables in predicting the FAs in the milk, contributing to the selection of the FA profile by the correlated response based on the physical profile of the milk. A total of 24 native goats, weighing 42 ± 4 kg and 30 ± 3 days into lactation, were used. The data were subjected to canonical analysis to identify the variables that best discriminate. The main objective of this procedure is to find the best set of variables to compose the discriminant function. Four components were needed to explain 70.68% of the total variation in the physical variables and FA profile in the milk of native goats. The percentage of variance accumulated in the first two factors is 41%. The most important variables in the first factor were the short-chain FAs, namely, caproic (6C), caprylic (8C), capric (10C), and lauric (C12), which are responsible for giving the milk its characteristic and even unpleasant odor, depending on their concentration. New studies with a larger sample of data should be carried out to better understand the relationships between physical and chemical variables in the milk of native goats as well as other breeds of goats for comparison. In addition, the weak simple correlations between the variables studied contributed to the results obtained.